2020
DOI: 10.1039/c9nr09654j
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous nickel sulfide nanoparticles anchored on N-doped graphene nanotubes with superior properties for high-performance supercapacitors and efficient oxygen evolution reaction

Abstract: Amorphous nickel sulfide nanoparticles electrodeposited on N-doped graphene nanotubes exhibit excellent electrochemical performance for asymmetric supercapacitors and the OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…A large number of studies have demonstrated that the OER activity of nickel sulfide can be improved by coupling with highly conductive materials such as nickel foam, [12a,15] graphene, [14,16] carbon nanotubes, [11b,13] and metal‐organic frames, [17] etc. Zou and co‐workers reported a synthetic method that leads to in situ growth of high‐index faceted Ni 3 S 2 nanosheet arrays on nickel foam (NF), with excellent OER catalytic activity and stability for the first time.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A large number of studies have demonstrated that the OER activity of nickel sulfide can be improved by coupling with highly conductive materials such as nickel foam, [12a,15] graphene, [14,16] carbon nanotubes, [11b,13] and metal‐organic frames, [17] etc. Zou and co‐workers reported a synthetic method that leads to in situ growth of high‐index faceted Ni 3 S 2 nanosheet arrays on nickel foam (NF), with excellent OER catalytic activity and stability for the first time.…”
Section: Methodsmentioning
confidence: 99%
“…Wang and co‐authors constructed layered 2D/2D NiS/graphene heterojunction structure, which exhibited high surface‐active sites and excellent conductivity, achieved by 300 mV overpotential at the current density of 10 mA cm −2 [16] . Li et al prepared thin NiS nanoparticles/N‐doped graphene nanotubes (for N‐GNT@NSN) heterojunction structure via a simple electrodeposition method, which the N‐GNT provides a fast channel for electronic transmission and promotes charge transfer to improves the catalytic activity of OER [11b] . Antonietti and co‐workers directly synthesized NiS nanosheets on stainless steel mesh materials, which demonstrated excellent OER catalytic performance [19] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations